Historical Review and Prospects for the Treatment of Hutchison-Gilford Syndrome (Eurasian Scientific Herald, 2023)
Progeria is a syndrome of premature aging, characterized by changes in the skin and internal organs. The term "progeria" was introduced by Dr. Gilford in 1904, who studied the clinical and morphological features of this pathology [1]. It occurs in both children and adults. Children have Hutchinson-Gilford Syndrome (SHG), adults have Werner Syndrome (WS). The disease is hereditary and is transmitted in an autosomal recessive manner, so isolated cases of brothers and sisters with progeria are explained by the fact that the parents were quite close relatives, for example, cousins, and the disease was the result of incestor. However, other causes of the disease are also called, for example: diencephalicpituitary insufficiency; secondary damage to several glands of the endocrine system; is the result of one of the manifestations of other endocrine hereditary diseases.